Topology optimization of adhesive material in a single lap joint using an evolutionary structural optimization method and a cohesive zone model as failure criterion. (April 2022) - Fernandes, Francisco Jose; Pavanello, Renato
This paper presents a study of the use of a structural optimization process coupled to a failure model in the adhesive material in single lap bonded joints. The critical point of these joints is in the region of the adhesive material, which performs the function of stress transmission between the structural elements. Owing to the single lap bonded joints shape, the applied loads are eccentric about the joint axis, resulting in a concentration of stress on the overlapping ends. In this study, numerical simulations in two and three dimensions were performed through finite element analysis to model an single lap bonded joints. An optimization procedure based on the bidirectional evolutionary structural optimization method was used to minimize the single lap bonded joints compliance under volume constraints. The design domain considered was restricted to the adhesive region. The cohesive zone model and the bidirectional evolutionary structural optimization method were simultaneously applied. The numerical results for two types of adhesives, with ductile and brittle failure behavior, enabled the establishment of mechanisms for determining the efficient positioning and quantity of adhesive materials.